Strategi Pembelajaran Aktif untuk Mengurangi Kebosanan Belajar Siswa di SMKS Muhammadiyah 9 Medan - Bintang Ariga (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Boredom during the learning process often becomes a significant barrier to students’ motivation and engagement, especially in vocational education settings. This phenomenon was also observed at SMKS Muhammadiyah 9 Medan, where some students demonstrated a lack of interest and active participation during learning activities. This study aims to analyze how the implementation of active learning strategies can reduce boredom and improve the quality of classroom interaction. A qualitative approach with a case study design was employed. Data were collected through semi-structured interviews with teachers and students, direct classroom observations, and supporting documentation. The data were analyzed inductively using thematic analysis to identify emerging patterns, trends, and meanings from teaching practices. The findings reveal that the application of active learning strategies—such as group discussions, project-based learning, problem solving, and the use of interactive learning media—positively impacts the learning process. These strategies not only enhance participation and learning motivation but also foster collaboration among students, improve teacher–student communication, and develop critical and social thinking skills. Furthermore, the classroom atmosphere becomes more dynamic, enjoyable, and participatory, significantly reducing learning boredom. Therefore, active learning strategies are proven to be relevant and effective in creating engaging, interactive, and meaningful learning experiences for students at SMKS Muhammadiyah 9 Medan. This research provides practical implications for teachers in selecting appropriate learning approaches to achieve educational goals more effectively.